Overuse Injury, Substance Use, and Resilience in Collegiate Female Athlete - Chelsea L Martin; Ellen Shanley; Chris Harnish; Amy M Knab; Shefali Christopher; Srikant Vallabhajosula; Garrett S Bullock (International Journal of Sports Physical Therapy)
# Background Overuse injury is a common stressor experienced by female collegiate athletes and is often underreported. In response, athletes may develop negative coping skills such as substance use. Alternatively, resilience is a modifiable trait that may positively influence response to musculoskeletal injuries and substance use.